The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0104-66322010000400014
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of zeolite a coatings on copper plates by using the substrate heating method

Abstract: -The substrate heating method was used to grow zeolite 4A coatings on copper plates. The reaction mixture was kept at 25°C, while the plate was heated to a higher temperature. In some of the synthesis experiments performed, the reaction mixture was circulated in the system. The coatings prepared were characterized by X-ray diffraction and scanning electron microscopy. It was demonstrated that crystalline and pure zeolite 4A coatings could be formed on copper by using the substrate heating method from a highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(24 reference statements)
1
3
0
Order By: Relevance
“…3. XRD results for commercial zeolite samples showed similar patterns as those obtained with the joint committee of powder diffraction standard powder diffraction database file and previous studies (Treacy and Higgins 2007;Teber et al 2010). Peaks typical of zeolite type A were found at 2θ = 7.1°, 10.1°, 22.4°, and 27.1° (Sharma et al 2012;Bieseki et al 2013).…”
Section: Resultssupporting
confidence: 81%
“…3. XRD results for commercial zeolite samples showed similar patterns as those obtained with the joint committee of powder diffraction standard powder diffraction database file and previous studies (Treacy and Higgins 2007;Teber et al 2010). Peaks typical of zeolite type A were found at 2θ = 7.1°, 10.1°, 22.4°, and 27.1° (Sharma et al 2012;Bieseki et al 2013).…”
Section: Resultssupporting
confidence: 81%
“…Song et al investigated the effect of alcohol content on MFI (silicalite-1 and ZSM-5) growth and found that, compared to growth in the absence of alcohol, the presence of alcohol induces the formation of smaller aggregates composed of many individual zeolite particles or of intergrowth zeolite particles, together with smaller crystal size . Tatlier et al proposed a substrate heating method for the preparation of zeolite coating. , They concluded that when nucleation on the substrate is promoted while that in the synthesis solution is suppressed, nucleation on the substrate dominates the synthesis process; thus, very open coatings with intercrystalline voids are formed. However, for the secondary growth of the seeds, the possible effect of ethanol was to promote additional nucleation over the primary seeds, which thus leads to the formation of additional nonzeolite pores, as evidenced by the slow crystal growth rate (see Figures S1 and S2 in Supporting Information).…”
Section: Results and Discussionmentioning
confidence: 99%
“…29 Tatlier et al proposed a substrate heating method for the preparation of zeolite coating. 30,31 They concluded that when nucleation on the substrate is promoted while that in the synthesis solution is suppressed, nucleation on the substrate dominates the synthesis process; thus, very open coatings with intercrystalline voids are formed. However, for the secondary growth of the seeds, the possible effect of ethanol was to promote additional nucleation over the primary seeds, which thus leads to the formation of additional nonzeolite pores, as evidenced by the slow crystal growth rate (see Figures S1 and S2 in Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the remarkably stable nature of stainless steel, even in highly alkaline and corrosive environments, this metal has been commonly used (Bonaccorsi and Proverbio, 2004;Fankhanel et al, 2009). Copper becomes less stable in the presence of high alkalinity, but this does not preclude the formation of thick coatings (Teber at al., 2010). The preparation of zeolite on aluminum involves the use of this metal as both the support and reactant in the reaction mixture (Calabrese et al, 2014).…”
Section: Introductionmentioning
confidence: 99%